KENDALA GURU KELAS RENDAH DALAM MENERAPKAN PEMBELAJARAN TEMATIK SEKOLAH DASAR NEGERI 66 PONTIANAK KOTA - Khairunnisa Khairunnisa; Hery Kresnadi; Asmayani Salimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
Abstrak:This study aims to describe the obstacles faced by low-grade teachers in implementing thematic learning at the 66 State Elementary School in Pontianak City. The research method is descriptive with a qualitative research form. Sources of research data were obtained from class III A teachers and class III B teachers. The research data were in the form of observation sheets, interviews and documentation. The data analysis technique is Miles and Huberman which includes four stages, namely data collection, data reduction, data presentation and conclusion drawing. The results showed that in applying thematic learning the teacher did not use lesson plans, limited learning media, and monotonous learning methods. Obstacles experienced by teachers in implementing thematic learning are lack of mastery of the material and developing material caused by the lack of teacher teaching materials, other obstacles are also difficulties for teachers to relate one lesson to the next lesson. The teacher's efforts when implementing thematic learning students have difficulty understanding the learning material, the teacher repeats the explanation of the material with different learning methods.